Crafting appropriate curricula in transnational education institutes: an integrative critical analysis - Butale, Chandapiwa (South African Journal of Higher Education, 2016)
The plethora of technological advancements in different communities of the world has created a scenario in which institutions of higher learning have decided to enhance their global appeal by making their programmes available to transnational students. Globalisation and the resultant growth of multinational corporations that demand skilled labour have also fuelled the emergence of transnational education institutions. This global phenomenon has compelled transnational institutions (TNIs) to revisit their curricula design processes. The marketisation of education, driven by issues of globalisation has motivated some traditionally single mode face-to-face institutions of higher learning to reconsider their teaching and learning strategies in order to remain relevant. This rethinking of strategy obviously impacts on curriculum reform in response to transnational education demands. This article endeavours to explore how TNIs take cognisance of the perspectives of multiracial and multicultural societies in crafting curricula that appeal to divergent student populations. It is argued that the rich and powerful capitalist (Western) forces will remain dominant in the creation of knowledge systems, while keeping the less privileged cultural influences on the periphery. The study used critical ontology (Foucault 1983) to assess the relationship between knowledge and power and their impact on the crafting of curricula for transnational students.